The reproductive biology of a tropical cyprinid, Hampala macrolepidota (Van Hasselt), from Zoo Negara Lake, Kuala Lumpur, Malaysia - Abidin, A.Z. (1986)
From a study on some aspects of the reproductive biology of the tropical cyprinid Hampala macrolepidota (Van Hasselt) in Zoo Negara Lake, Kuala Lumpur, Malaysia, analyses of the maturity stages, gonadosomatic indices and oocyte diameter patterns show that this fish is able to spawn throughout the year. However, physicochemical and environmental factors determine the actual spawning time of this fish. Spawning activity is associted with decreasing temperatures and daylengths, rising water levels and increasing turbidities. Spawning is protracted and coincides with the rainy season which extends from November to March the following year. Copyright © 1986, Wiley Blackwell. All rights reserved